2021
DOI: 10.15195/v8.a8
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Women’s Role-Taking Accuracy: How Status Matters

Abstract: Role-taking is the process of mentally and affectively placing the self in the position of another, understanding the world from the other's perspective. Role-taking serves an expressive function within interpersonal interaction, supporting others to pursue instrumental tasks that are recognized, valued, and rewarded. In the present work, we compare role-taking accuracy between white women and black women across status-varying interactional arrangements. Data for this study come from a series of two laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Future research should examine intersections of race, gender, and class to understand perspective taking intersectionally. Although some research has shown that Black women are more attuned to others’ situations than White women (see Love and Davis 2021), we know little about such intersections among children or among boys. For example, would younger boys be more able or willing to take the perspective of others if asked about the best things about being White or Black boys?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research should examine intersections of race, gender, and class to understand perspective taking intersectionally. Although some research has shown that Black women are more attuned to others’ situations than White women (see Love and Davis 2021), we know little about such intersections among children or among boys. For example, would younger boys be more able or willing to take the perspective of others if asked about the best things about being White or Black boys?…”
Section: Discussionmentioning
confidence: 99%
“…Collective guilt induces denial for those with privilege, but people who are disadvantaged by gender stereotypes also have reasons to resist thinking privileges exist; this way, they can continue to imagine they can get ahead on their own merits (Ellemers 2018:290). This one-sided perspective taking is problematic, because as Love and Davis (2021) noted, perspective taking (or “role taking”) is a crucial element of societal maintenance in that it “strengthens social cohesion, reduces stereotypes, increases helping behavior, and supports positive out-group evaluations” (p. 152).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Role-taking is the process and practice of putting the self in the proverbial shoes of another—understanding the world from the other’s perspective and behaviorally responding in turn. Role-taking serves as a fundamental building block of the social–psychology paradigm, underpinning structurally situated social interactions in which individuals present, interpret, and respond to meaningful social cues (Cast 2004; Davis and Love 2017; Love and Davis 2014, 2021; Mead 1934; Turner 1962).…”
Section: Literaturementioning
confidence: 99%
“…Research shows that role-taking variations are not random but fall along status lines. In particular, those with higher status within the social structure (e.g., men, white people, those in leadership positions) role-take less actively compared to their lower status counterparts (Dietze & Knowles, 2021;Adam D. Galinsky, Magee, Inesi, & Gruenfeld, 2006;Love & Davis, 2021;Thomas, 1972;van Kleef et al, 2008;Zaki, 2018).…”
Section: Role-takingmentioning
confidence: 99%